Evaluation of variants in the ENTPD1 and ENTPD2 genes in athletic horses with exercise-induced pulmonary haemorrhage - Leite, Raíssa Oliveira [UNESP]; Albertino, Lukas Garrido [UNESP]; Sperandio, Lídia Maria Santos [UNESP]; Campos, Fernanda; Campos, Reinaldo; Borges, Alexandre Secorun [UNESP]; Oliveira-Filho, José Paes [UNESP] (Springer Nature, 2024)
Background: Exercise-induced pulmonary haemorrhage (EIPH) in athletic horses is characterized by the presence of blood from the lungs in the tracheobronchial tree after intense exercise. Despite the high prevalence of EIPH in horses, the primary aetiology remains unknown. Variants in the genes encoding CD39 and CD39L1 (ENTPD1 and ENTPD2, respectively) were previously reported as potential genetic causes involved in EIPH pathogenesis. However, the role of these variants in haemostatic functions is unknown. Results: To investigate the association between EIPH and missense variants in the ENTPD1 (rs1152296272, rs68621348, and rs68621347) and ENTPD2 genes (rs782872967), 76 Thoroughbred horses diagnosed with EIPH and 56 without clinical signs of EIPH (control group) by trachea-bronchial endoscopy were genotyped. The rs1152296272 and rs68621347 variants were linked, which explained why the same results were found in all horses. Approximately 96% and 95% of the EIPH and control horses, respectively, carried at least one nonreference allele for these variants. In contrast, 100% of the control horses and 96% of the EIPH horses were homozygous for the reference allele for the rs68621348 variant. In the EIPH group, 1.5% of the horses were homozygotes and 24% were heterozygous for the nonreference allele of the rs782872967 variant. In the control group, the nonreference allele of this variant was observed only in heterozygotes (16%). There were no significant differences between groups for any of the variants. Conclusions: The variants previously described in the genes encoding the CD39 and CD39L1 enzymes were highly present in the studied population. However, no association was found between the occurrence of EIPH and the presence of these variants in Thoroughbred horses in this study.
Keywords: Athletic horse; Epistaxis; Genetic disease; Haemorrhage; Haemostasis